Amine-catalyzed and functional group-controlled chemo- and regioselective synthesis of multi-functionalized CF3-benzene via a metal-free process. Issue 22 (28th October 2019) - Peng, Fu; Zhao, Qian; Huang, Wei; Liu, Shuai-Jiang; Zhong, Ya-Jun; Mao, Qing; Zhang, Nan; He, Gu; Han, Bo
Abstract : A novel strategy for the synthesis of CF3 -containing multi-substituted benzenes with high chemo- and regioselectivities under metal-free and air-tolerant conditions was established. Abstract : A new strategy for the preparation of CF3 -containing multi-substituted benzene compounds via an amine-catalyzed reaction under metal-free and air-tolerant conditions was developed. This green reaction provides a functional group-controlled synthetic strategy, and the polysubstituted benzene derivatives were obtained in moderate to good yields. Using a tri-substituted alkene containing a cyano group as the starting material, CF3 -functionalized benzene compounds with four adjacent substituents can be formed via a Rauhut–Currier (RC) reaction-triggered [3 + 3] cascade. When the cyano group is replaced with a benzoyl group, Michael-initialized [4 + 2] aromatization occurs, producing the corresponding CF3 -benzene with five contiguous substituent groups. The reaction also features numerous advantages, including excellent chemo- and regioselectivity, extensive substrate scope, and environmentally friendly conditions. A simple conversion of an aldehyde into a terminal alkyne was also achieved, and the utility of this environmentally compatible method and the one-pot reaction was demonstrated by synthesizing a CF3 -functionalized benzene–zidovudine hybrid.